2020
DOI: 10.1186/s12902-020-0516-7
|View full text |Cite
|
Sign up to set email alerts
|

Statin prescription among patients with type 2 diabetes in Botswana: findings and implications

Abstract: Background: There is evidence of statin benefit among patients with diabetes regardless of cholesterol levels or prior cardiovascular disease history. Despite the evidence, there is under-prescription of statins in clinical practice. This study aimed to assess statin prescriptions and associated factors among patients with type 2 diabetes in Botswana. Methods: The study was a secondary data analysis of 500 randomly selected type 2 diabetes patients at a specialised diabetes clinic at Gaborone, Botswana. We ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
3
11
3
1
Order By: Relevance
“…It was found that statins were prescribed in about half of the participants with T2DM who were eligible for prescription. Findings of this study were similar to those found by Mwita et al, 32 Demoz et al 33 and Gupta et al 23 and in which statin prescriptions were 45.5% and 55.7%, respectively. The explanation for such a low prescription rate could be due to the following reasons: firstly, lack of local guidelines, secondly, inadequate adherence to already recommended international guidelines, 33 , 34 and thirdly, limited access to medications and lipid tests due to poor socioeconomic status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was found that statins were prescribed in about half of the participants with T2DM who were eligible for prescription. Findings of this study were similar to those found by Mwita et al, 32 Demoz et al 33 and Gupta et al 23 and in which statin prescriptions were 45.5% and 55.7%, respectively. The explanation for such a low prescription rate could be due to the following reasons: firstly, lack of local guidelines, secondly, inadequate adherence to already recommended international guidelines, 33 , 34 and thirdly, limited access to medications and lipid tests due to poor socioeconomic status.…”
Section: Discussionsupporting
confidence: 92%
“…Of those patients who received statins (n = 187), moderate intensity statins prescription was the only pattern found in 47.3%, similarly to 46.1% in the study done by Dermoz et al 32 Likewise, almost half of patients (166; 47.7%) in a high risk group (n = 348) were prescribed with moderate-dose statins, contrary to the recommendations 12 , 35 while more than half in this group did not receive statins despite being at high risk.…”
Section: Discussionsupporting
confidence: 76%
“…This compares to findings of Mwita et al in the same clinic in Botswana who found 45.5% of eligible diabetes patients were on statins. 73 Our findings are also worse than those of diabetic HIV-infected patients in Tanzania where approximately one-third of patients were on statins. Our results emphasize the need to remind physicians even in a tertiary care setting on the importance of prescribing statins to reduce LDL-C levels and subsequent cardiovascular events in eligible patients, and we will be following this up.…”
Section: Discussioncontrasting
confidence: 62%
“…Statins have been demonstrated to reduce the risk of CV events and death in people with DM when given as primary or secondary prevention [ 61 , 62 ]. Consequently, not prescribing a statin therapy to an eligible adult with DM was considered as inappropriate in 28 included studies [ 2 , 24 34 , 58 , 63 – 74 ], (Diab MI, unpublished; Aketchi IE, unpublished; Langenhoven W, unpublished).…”
Section: Discussionmentioning
confidence: 99%